Problemas elípticos superlineares com não linearidades assimétricas - Rosa, Wallisom da Silva (2015)
The aim of this work is to present results of existence of solutions for a class of nonlinear asymmetryc elliptic problems. The asymmetry that we consider here has linear behavior on - infnity and superlinear on + infnity. To obtain these results we apply variational methods as linking theorems and topological methods like topological degree theory.